71-3=3+6a

Simple and best practice solution for 71-3=3+6a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 71-3=3+6a equation:


Simplifying
71 + -3 = 3 + 6a

Combine like terms: 71 + -3 = 68
68 = 3 + 6a

Solving
68 = 3 + 6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6a' to each side of the equation.
68 + -6a = 3 + 6a + -6a

Combine like terms: 6a + -6a = 0
68 + -6a = 3 + 0
68 + -6a = 3

Add '-68' to each side of the equation.
68 + -68 + -6a = 3 + -68

Combine like terms: 68 + -68 = 0
0 + -6a = 3 + -68
-6a = 3 + -68

Combine like terms: 3 + -68 = -65
-6a = -65

Divide each side by '-6'.
a = 10.83333333

Simplifying
a = 10.83333333

See similar equations:

| 6.5/12.3=x/9.8 | | -3x^2+26x=16 | | -13-8=x-2 | | 3.50x+10=5.25x-11 | | -11x=6x+15 | | 1w-(-43.7)=-3.674 | | 6(4x-4)=3(8x+1) | | 5x^4-16x^3-21x^2=0 | | 11x=7x+36 | | -(5y+1)-(-4y-7)=1 | | x+x+3+x+3+5=19 | | 2/3x=15-1/3x | | 2z=-50 | | (x^2+5x+2)(x^2+5x+2)-4(x^2+5x+2)-32=0 | | c=8*8+13*13 | | 12x-8x=20 | | 12x^2-960x+14400=0 | | 0x+5=0x+5 | | -56=1c-(-8) | | 4xy-x(y-3)= | | -8n+4(1+5n)=-6n+14 | | (a+4)2=a | | -6.7=1y-27 | | 17-2x=17-2x | | -3+5=-3(9x+1) | | 1b+-9=36 | | 5x^3-16x^2-21x=0 | | 7.5/4.3=X/3.75 | | (-8)-3(-5)= | | 40+15+0.25(100)=45+0.35(100) | | 2/5y=1/5x+8/5 | | x^3+2x=144 |

Equations solver categories